A novel alginate-gelatin microcapsule to enhance bone differentiation of mesenchymal stem cells. Issue 6 (13th April 2022) - Samadian, Sohrab; Karbalaei, Atiyeh; Pourmadadi, Mehrab; Yazdian, Fatemeh; Rashedi, Hamid; Omidi, Meisam; Malmir, Samira
Abstract: Some designed macromolecules may be suitable substitutes for damaged tissue. This study aimed to use a novel Carbon Quantum Dots (CQD)-Alginate-Gelatin nanocomposite (NC) in the form of the microcapsule and as a scaffold for differentiation of mesenchymal stem cells into bone tissue. The CQD nanoparticles (NPs) were synthesized by the hydrothermal method and were characterized by FTIR, zeta potential, and DLS analysis. Alginate was used as a porous and flexible basis for the proper nutrition of the cells and keeping them safe from the body's immune system. To improve the biodegradability of CQD-alginate NC, gelatin protein was added to the NC. The CQD was employed at the concentration of 100 μg/ml and after placing the cells in the NC, microcapsules were made using the microdroplet technique. The binding and proliferation of mesenchymal stem cells (MSCs) in microcapsules were examined by DAPI staining and MTT. Also, bone differentiation of proliferated MSCs was investigated by evaluating the activity of alkaline phosphatase. The results showed that Alginate-Gelatin NC with its unique structure has an effective role in MSCs osteogenesis. Consequently, Alginate-Gelatin NC has been a perfect base for the performance of CQD NPs, so that, CQD-Alginate-Gelatin NC osteogenesis is higher than that of Alginate-Gelatin (CQD-free) composites after 14 days. Graphical abstract: UF0001